Polarization-transparent silicon photonic add-drop multiplexer with wideband hitless tuneability - Francesco Morichetti (Nature Portfolio, 2021)
Reconfigurable wavelength-selective devices are essential components of flexible optical networks. Here the authors show a silicon-photonic add-drop multiplexer meeting the strict requirements of telecom systems in terms of broadband operation range, hitless tunability and polarization transparency.